Makam Sitor Situmorang untuk Danau Toba: Kajian sastra pariwisata - Simanihuruk, Bertova; Lariesto, Pioro Benevolent; Simamora, Rosa Maria (Universitas Mulawarman, 2026)
This study aims to analyze the potential of Sitor Situmorang’s grave in Turpuk Sihotang Village, Samosir Regency, to increase tourist visits and length of stay at Lake Toba. Using a descriptive qualitative methodology, this field research collects primary data through interviews and observations, supported by secondary data sourced from journals, online news, and books. Data analysis is conducted using a literary tourism approach. The results shows that Sitor Situmorang’s grave has great potential to transform into a prominent literary and cultural tourism destination. However, to realize this potential, a comprehensive and integrated development strategy is needed. This includes building strategic partnerships with all relevant parties. Development should be oriented towards the concept of Integrated Literary Tourism by creating literary routes, thematic tour packages, cross-destination collaboration, and literary festival. Thus, the grave will not only become a pilgrimage site, but also a dynamic center for cultural heritage preservation and a driver of the local economy, ultimately leading to a significant increase in tourist visits and length of stay.